Design and develop instrumentation system for free fall impact machine - Rahmat Hidayat Arifai (2022)
Development of instrumentation system for free-fall impact machine was carried out. The instrumentation system was developed to obtain experimental data on impact energy absorbed by polymer composite material. During the development of the instrumentation system, the development standard was taken into consideration where the standard of ASTM D7136/D7136M was being used in this project. Besides, the SOLIDWORKS software was used to model and verify the mechanical component using the CAE application. The component of the instrumentation is including the load cell that detects the impact force on the specimen and the signal amplifier that amplified the output signal. As result, a graph of force against time was displayed digitally with the use of a data acquisition system. Therefore, the constructed instrumentation system for the free-fall impact machine was able to measure up to 9.5 kN of impact force and 33.86 J of impact energy. The coefficient of a variant of data produced from this instrumented free-fall impact machine is below 5%. The accuracy of the impact energy instrumentation system shows a small error percentage which is below than 3% percentage between 0.2m to 0.4m of drop height.